The Role of IGRA Professional Organization in Improving Pedagogical and Professional Competence of RA Teachers - Rahayuliana Rahayuliana; Irma Yuliantina (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research focuses on determining the role of the IGRA professional organization in improving the pedagogical and professional competence of RA teachers. This research uses a qualitative approach with descriptive methods. The sample selection used a purposive sampling method, namely the researcher chose research subjects that were appropriate and specific to their profession. The primary data source for this research came from 124 respondents consisting of 9 IGRA Regional Leadership administrators (PD IGRA), 11 IGRA Branch Leadership administrators (PC IGRA), 41 school principals and 63 RA teachers in the city of Batam. This research begins in October 2023 until December 2023. Data collection techniques use interviews distributed via the Google Form application and field observations. The results of this research show that the professional organization IGRA has played a role in improving the pedagogical and professional competence of RA teachers through outreach activities, workshops/training and assistance in the Implementation of the Independent Raudhatul Athfal Curriculum (IKM RA). This is proven by the implementation of the Merdeka curriculum in all RA cities of Batam